Anomalous Anisotropic Magnetoresistance of Antiferromagnetic Epitaxial Bimetallic Films: Mn2Au and Mn2Au/Fe Bilayers. (22nd June 2016) - Wu, Han‐Chun; Abid, Mohamed; Kalitsov, Alan; Zarzhitsky, Pavel; Abid, Mourad; Liao, Zhi‐Min; Coileáin, Cormac Ó; Xu, Hongjun; Wang, Jing‐Jing; Liu, Huajun; Mryasov, Oleg N.; Chang, Ching‐Ray; et al.
Abstract : Recently intensive efforts have been devoted to the emerging field of antiferromagnetic (AFM) spintronics, where ferromagnetic electrodes are substituted by antiferromagnets. This study investigates the anisotropic magnetoresistance (AMR) of epitaxial tetragonal antiferromagnetic bimetallic films: Mn2 Au and Mn2 Au/Fe bilayers. An anomalous AMR effect with additional peaks is observed. This study theoretically and experimentally demonstrates that the AFM spins of Mn2 Au can be viewed and controlled at room temperature, and this is achievable with a notably relatively small magnetic field of 200 mT. Strong hybridization between Au and Mn, and strong modification of the intrinsic quadratic anisotropy of Mn2 Au from interfacial biquadratic anisotropy result in an additional anomalous AMR component of 1%. The findings suggest that Mn2 Au films can be used in room temperature antiferromagnetic spintronics. Abstract : Mn2 Au, a bimetallic antiferromagnet, is considered an interesting high Néel temperature candidate within the emerging field of antiferromagnetic spintronic devices. An anomalous anisotropic magnetoresistance effect is observed with four peaks, persisting to room‐temperature for a field as low as 200 mT, demonstrating how Mn2 Au spins can be viewed and controlled at room‐temperature and offering a route to room‐temperature antiferromagnetic spintronics.